Phase 1 Pharmacokinetic Trial of 2 Intravaginal Rings Containing Different Dose Strengths of Vicriviroc (MK-4176) and MK-2048. (4th October 2018) - Liu, Albert Y; Zhang, Jingyang; Anderson, Peter L; Wagner, Theresa; Pan, Zhenyu; Peda, Melissa; Gomez, Kailazarid; Beamer, May; Jacobson, Cindy; Strizki, Julie; Dezzutti, Charlene S; Piper, Jeanna M; et al.
Abstract: Background: Vaginal rings (VRs) are a promising approach for sustained delivery of antiretroviral (ARV) medication to prevent human immunodeficiency virus (HIV) infection in women. Combination ARV VRs could increase efficacy. Methods: MTN-028, a phase 1 trial in 19 HIV-uninfected women, evaluated 2 VRs containing vicriviroc (VCV) and MK-2048. Participants were randomized 2:1 to a low-dose (VCV, 91 mg; MK-2048, 10 mg) or original-dose (VCV, 182 mg; MK-2048, 30 mg) ring used for 28 days. Safety was assessed by documenting adverse events (AEs). Drug concentrations were evaluated in plasma, cervicovaginal fluid (CVF), and cervical tissue samples. Results: All AEs reported were grade 1 or 2, with no statistically significant differences in related genitourinary AEs or grade ≥2 AEs observed between arms (P = >.99). VCV/MK-2048 concentrations rose rapidly, with higher plasma area under the concentration-time curve (AUC) in the original-dose arm (geometric mean ratio, 3.29 for VCV and 1.49 for MK-2048) and similar AUCs across arms for CVF samples. Cervical tissue concentrations were higher in the original-dose arm (geometric mean ratio, 7.94 for VCV and 6.45 for MK-2048), with greater drug released based on residual drug levels. Plasma and CVF concentrations for both drugs fell rapidly after ring removal. Conclusions: In this first study evaluating 2 doses of a combination VCV/MK-2048 VR, both rings were found to be safe and well tolerated. VCV and MK-2048 were detectable in plasma, CVF, and cervical tissue samples, and drug release and plasma drug exposure were higher for the original-dose than for the low-dose ring. Abstract : This study evaluated 2 dose strengths of a novel combination antiretroviral vaginal ring containing vicriviroc and MK-2048. Both rings were found to be safe and well tolerated. Drug release and plasma drug exposure were higher with the original than with the low-dose ring.